Acid Sphingomyelinase Impacts Canonical Transient Receptor Potential Channels 6 (TRPC6) Activity in Primary Neuronal Systems - Zeitler, Stefanie; Schumacher, Fabian; Monti, Juliana; Anni, Daniela; Guhathakurta, Debarpan; Kleuser, Burkhard; Friedland, Kristina; Fejtová, Anna; Kornhuber, Johannes; Rhein, Cosima (Cells, 2020)
: The acid sphingomyelinase (ASM)/ceramide system exhibits a crucial role in the pathology of major depressive disorder (MDD). ASM hydrolyzes the abundant membrane lipid sphingomyelin to ceramide that regulates the clustering of membrane proteins via microdomain and lipid raft organization. Several commonly used antidepressants, such as fluoxetine, rely on the functional inhibition of ASM in terms of their antidepressive pharmacological effects. Transient receptor potential canonical 6 (TRPC6) ion channels are located in the plasma membrane of neurons and serve as receptors for hyperforin, a phytochemical constituent of the antidepressive herbal remedy St. John's wort. TRPC6 channels are involved in the regulation of neuronal plasticity, which likely contributes to their antidepressant effect. In this work, we investigated the impact of reduced ASM activity on the TRPC6 function in neurons. A lipidomic analysis of cortical brain tissue of ASM deficient mice revealed a decrease in ceramide/sphingomyelin molar ratio and an increase in sphingosine. In neurons with ASM deletion, hyperforin-mediated Ca2+-influx via TRPC6 was decreased. Consequently, downstream activation of nuclear phospho-cAMP response element-binding protein (pCREB) was changed, a transcriptional factor involved in neuronal plasticity. Our study underlines the importance of balanced ASM activity, as well as sphingolipidome composition for optimal TRPC6 function. A better understanding of the interaction of the ASM/ceramide and TRPC6 systems could help to draw conclusions about the pathology of MDD.
CRIS-Team Scopus Importer:2020-12-04
Keywords: acid sphingomyelinase; major depressive disorder; sphingolipids; trpc6

Aβ1-16 controls synaptic vesicle pools at excitatory synapses via cholinergic modulation of synapsin phosphorylation - Anni, Daniela; Weiss, Eva-Maria; Guhathakurta, Debarpan; Akdas, Enes Yagiz; Klueva, Julia; Zeitler, Stefanie; Andres-Alonso, Maria; Huth, Tobias; Fejtová, Anna (Cellular and Molecular Life Sciences, 2021)
Amyloid beta (Aβ) is linked to the pathology of Alzheimer’s disease (AD). At physiological concentrations, Aβ was proposed to enhance neuroplasticity and memory formation by increasing the neurotransmitter release from presynapse. However, the exact mechanisms underlying this presynaptic effect as well as specific contribution of endogenously occurring Aβ isoforms remain unclear. Here, we demonstrate that Aβ1-42 and Aβ1-16, but not Aβ17-42, increased size of the recycling pool of synaptic vesicles (SV). This presynaptic effect was driven by enhancement of endogenous cholinergic signalling via α7 nicotinic acetylcholine receptors, which led to activation of calcineurin, dephosphorylation of synapsin 1 and consequently resulted in reorganization of functional pools of SV increasing their availability for sustained neurotransmission. Our results identify synapsin 1 as a molecular target of Aβ and reveal an effect of physiological concentrations of Aβ on cholinergic modulation of glutamatergic neurotransmission. These findings provide new mechanistic insights in cholinergic dysfunction observed in AD.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Alpha7 nicotinic acetylcholine receptor; Amyloid beta; Synapsin 1; Synaptic vesicle dynamics

Bassoon controls synaptic vesicle release via regulation of presynaptic phosphorylation and cAMP - Montenegro-Venegas, Carolina; Guhathakurta, Debarpan; Pina-Fernandez, Eneko; Andres-Alonso, Maria; Plattner, Florian; Gundelfinger, Eckart D.; Fejtova, Anna (EMBO Reports, 2022)
Neuronal presynaptic terminals contain hundreds of neurotransmitter-filled synaptic vesicles (SVs). The morphologically uniform SVs differ in their release competence segregating into functional pools that differentially contribute to neurotransmission. The presynaptic scaffold bassoon is required for neurotransmission, but the underlying molecular mechanisms are unknown. We report that glutamatergic synapses lacking bassoon feature decreased SV release competence and increased resting pool of SVs as assessed by imaging of SV release in cultured neurons. CDK5/calcineurin and cAMP/PKA presynaptic signalling are dysregulated, resulting in an aberrant phosphorylation of their downstream effectors synapsin1 and SNAP25, well-known regulators of SV release competence. An acute pharmacological restoration of physiological CDK5 and cAMP/PKA activity fully normalises the SV pools in neurons lacking bassoon. Finally, we demonstrate that CDK5-dependent regulation of PDE4 activity interacts with cAMP/PKA signalling and thereby controls SV release competence. These data reveal that bassoon organises SV pools in glutamatergic synapses via regulation of presynaptic phosphorylation and cAMP homeostasis and indicate a role of CDK5/PDE4/cAMP axis in the control of neurotransmitter release.
CRIS-Team Scopus Importer:2022-07-08
Keywords: Bassoon; neuromodulation; neurotransmission; PDE4; synaptic vesicle recycling

CRISPR/Cas9-mediated generation of hESC lines with homozygote and heterozygote p.R331W mutation in CTBP1 to model HADDTS syndrome - Akdas, Enes Yagiz; Turan, Sören; Guhathakurta, Debarpan; Ekici, Arif Bülent; Salar, Seda; Lie, Dieter Chichung; Winner, Beate; Fejtová, Anna (Stem Cell Research, 2023)
C-terminal Binding Protein 1 (CTBP1) is a ubiquitously expressed transcriptional co-repressor and membrane trafficking regulator. A recurrent de novo c.991C>T mutation in CTBP1 leads to expression of p.R331W CTBP1 and causes hypotonia, ataxia, developmental delay, and tooth enamel defects syndrome (HADDTS), a rare early onset neurodevelopmental disorder. We generated hESCs lines with heterozygote and homozygote c.991C>T in CTBP1 using CRISPR/Cas9 genome editing and validated them for genetic integrity, off-target mutations, and pluripotency. They will be useful for investigation of HADDTS pathophysiology and for screening for potential therapeutics.
CRIS-Team Scopus Importer:2023-01-20

CtBP1-Mediated Membrane Fission Contributes to Effective Recycling of Synaptic Vesicles - Ivanova, Daniela; Imig, Cordelia; Camacho, Marcial; Reinhold, Annika; Guhathakurta, Debarpan; Montenegro-Venegas, Carolina; Cousin, Michael A.; Gundelfinger, Eckart D.; Rosenmund, Christian; Cooper, Benjamin; Fejtova, Anna (Cell Reports, 2020)
Compensatory endocytosis of released synaptic vesicles (SVs) relies on coordinated signaling at the lipid-protein interface. Here, we address the synaptic function of C-terminal binding protein 1 (CtBP1), a ubiquitous regulator of gene expression and membrane trafficking in cultured hippocampal neurons. In the absence of CtBP1, synapses form in greater density and show changes in SV distribution and size. The increased basal neurotransmission and enhanced synaptic depression could be attributed to a higher vesicular release probability and a smaller fraction of release-competent SVs, respectively. Rescue experiments with specifically targeted constructs indicate that, while synaptogenesis and release probability are controlled by nuclear CtBP1, the efficient recycling of SVs relies on its synaptic expression. The ability of presynaptic CtBP1 to facilitate compensatory endocytosis depends on its membrane-fission activity and the activation of the lipid-metabolizing enzyme PLD1. Thus, CtBP1 regulates SV recycling by promoting a permissive lipid environment for compensatory endocytosis. Ivanova et al. demonstrate a dual role of CtBP1 in synaptic transmission. Nuclear CtBP1 restricts synaptogenesis and vesicular release probability, whereas presynaptic CtBP1 promotes compensatory endocytosis via activation of the lipid enzyme PLD1. Phosphorylation by Pak1 controls the redistribution of CtBP1 from active zones toward endocytic sites linking presynaptic exo- and endocytosis.
CRIS-Team Scopus Importer:2020-02-25
Keywords: Bassoon; compensatory endocytosis; CtBP1; exo-endocytosis coupling; membrane fission; Pak1; PLD1; presynapse; synaptic vesicle pools; synaptic vesicle recycling

Developmental effect of RASopathy mutations on neuronal network activity on a chip - Weiss, Eva-Maria; Guhathakurta, Debarpan; Petrušková, Aneta; Hundrup, Verena; Zenker, Martin; Fejtová, Anna (Frontiers in Cellular Neuroscience, 2024)
RASopathies are a group of genetic disorders caused by mutations in genes encoding components and regulators of the RAS/MAPK signaling pathway, resulting in overactivation of signaling. RASopathy patients exhibit distinctive facial features, cardiopathies, growth and skeletal abnormalities, and varying degrees of neurocognitive impairments including neurodevelopmental delay, intellectual disabilities, or attention deficits. At present, it is unclear how RASopathy mutations cause neurocognitive impairment and what their neuron-specific cellular and network phenotypes are. Here, we investigated the effect of RASopathy mutations on the establishment and functional maturation of neuronal networks. We isolated cortical neurons from RASopathy mouse models, cultured them on multielectrode arrays and performed longitudinal recordings of spontaneous activity in developing networks as well as recordings of evoked responses in mature neurons. To facilitate the analysis of large and complex data sets resulting from long-term multielectrode recordings, we developed MATLAB-based tools for data processing, analysis, and statistical evaluation. Longitudinal analysis of spontaneous network activity revealed a convergent developmental phenotype in neurons carrying the gain-of-function Noonan syndrome-related mutations Ptpn11D61Y and KrasV14l. The phenotype was more pronounced at the earlier time points and faded out over time, suggesting the emergence of compensatory mechanisms during network maturation. Nevertheless, persistent differences in excitatory/inhibitory balance and network excitability were observed in mature networks. This study improves the understanding of the complex relationship between genetic mutations and clinical manifestations in RASopathies by adding insights into functional network processes as an additional piece of the puzzle.
CRIS-Team Scopus Importer:2024-06-28
Keywords: excitation/inhibition balance; mouse models; multielectrode array; network establishment and maturation; neurodevelopmental disorder; Noonan syndrome; principal component analysis; rare diseases

Development and Application of Automatized Routines for Optical Analysis of Synaptic Activity Evoked by Chemical and Electrical Stimulation. - Fejtová, Anna; Guhathakurta, Debarpan; Akdas, Enes Yagiz; Weiss, Eva-Maria (Frontiers in Bioinformatics, 2022)
The recent development of cellular imaging techniques and the application of genetically encoded sensors of neuronal activity led to significant methodological progress in neurobiological studies. These methods often result in complex and large data sets consisting of image stacks or sets of multichannel fluorescent images. The detection of synapses, visualized by fluorescence labeling, is one major challenge in the analysis of these datasets, due to variations in synapse shape, size, and fluorescence intensity across the images. For their detection, most labs use manual or semi-manual techniques that are time-consuming and error-prone. We developed SynEdgeWs, a MATLAB-based segmentation algorithm that combines the application of an edge filter, morphological operators, and marker-controlled watershed segmentation. SynEdgeWs does not need training data and works with low user intervention. It was superior to methods based on cutoff thresholds and local maximum guided approaches in a realistic set of data. We implemented SynEdgeWs in two automatized routines that allow accurate, direct, and unbiased identification of fluorescently labeled synaptic puncta and their consecutive analysis. SynEval routine enables the analysis of three-channel images, and ImgSegRout routine processes image stacks. We tested the feasibility of ImgSegRout on a realistic live-cell imaging data set from experiments designed to monitor neurotransmitter release using synaptic phluorins. Finally, we applied SynEval to compare synaptic vesicle recycling evoked by electrical field stimulation and chemical depolarization in dissociated cortical cultures. Our data indicate that while the proportion of active synapses does not differ between stimulation modes, significantly more vesicles are mobilized upon chemical depolarization.
EVALuna2:523130

Hydroxynorketamine, but not ketamine, acts via α7 nicotinic acetylcholine receptor to control presynaptic function and gene expression - Guhathakurta, Debarpan; Petrušková, Aneta; Akdas, Enes Yagiz; Perelló Amorós, Bartomeu; Frischknecht, Renato; Anni, Daniela; Weiss, Eva-Maria; Walter, Martin; Fejtová, Anna (Translational Psychiatry, 2024)
Ketamine is clinically used fast-acting antidepressant. Its metabolite hydroxynorketamine (HNK) shows a robust antidepressant effect in animal studies. It is unclear, how these chemically distinct compounds converge on similar neuronal effects. While KET acts mostly as N-methyl-d-aspartate receptor (NMDAR) antagonist, the molecular target of HNK remains enigmatic. Here, we show that KET and HNK converge on rapid inhibition of glutamate release by reducing the release competence of synaptic vesicles and induce nuclear translocation of pCREB that controls expression of neuroplasticity genes connected to KET- and HNK-mediated antidepressant action. Ro25-6981, a selective antagonist of GluN2B, mimics effect of KET indicating that GluN2B-containing NMDAR might mediate the presynaptic effect of KET. Selective antagonist of α7 nicotinic acetylcholine receptors (α7nAChRs) or genetic deletion of Chrna7, its pore-forming subunit, fully abolishes HNK-induced synaptic and nuclear regulations, but leaves KET-dependent cellular effects unaffected. Thus, KET or HNK-induced modulation of synaptic transmission and nuclear translocation of pCREB can be mediated by selective signaling via NMDAR or α7nAChRs, respectively. Due to the rapid metabolism of KET to HNK, it is conceivable that subsequent modulation of glutamatergic and cholinergic neurotransmission affects circuits in a cell-type-specific manner and contributes to the therapeutic potency of KET. This finding promotes further exploration of new combined medications for mood disorders.
CRIS-Team Scopus Importer:2024-01-26

Rasopathy-Associated Mutation Ptpn11D61Y has Age-Dependent Effect on Synaptic Vesicle Recycling - Guhathakurta, Debarpan; Selzam, Franziska; Petrušková, Aneta; Weiss, Eva-Maria; Akdas, Enes Yagiz; Montenegro-Venegas, Carolina; Zenker, Martin; Fejtová, Anna (Cellular and Molecular Neurobiology, 2024)
Rasopathies are genetic disorders often associated with developmental delay and intellectual disability. Noonan syndrome (NS) is one of the most common Rasopathies, caused by mutations in PTPN11 in more than 50% of cases. In mammalian neurons, PTPN11 controls the trafficking of postsynaptic glutamate receptors. This process is disrupted in neurons expressing PTPN11 variants associated with Rasopathies and is thought to contribute to the cognitive impairments in Noonan syndrome. Recent work revealed presynaptic impairments upon expression of RASopathy-linked PTPN11 variants in Drosophila. However, the presynaptic role of PTPN11 has not yet been addressed in mammals. Here, we investigated membrane trafficking of synaptic vesicles in cultured mouse cortical neurons expressing Rasopathy-associated PTPN11D61Y variant. We observed a significantly smaller readily releasable and total recycling pool of synaptic vesicles. The drop in synaptic vesicle release competence was accompanied by a decreased rate of SV retrieval. Interestingly, the presynaptic phenotype was evident in mature (DIV21) but not in immature (DIV12) neurons. Thus, our data reveal importance of balanced PTPN11 activity for normal trafficking of neurotransmitter-filled synaptic vesicles in the presynaptic ending of mature neurons.
CRIS-Team Scopus Importer:2024-11-29